2013
DOI: 10.3121/cmr.2013.1156
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Prostate Cancer Survivors in a Diabetic Cohort: Results from the Living With Diabetes Study

Abstract: Objective: Diabetes is more common in cancer survivors than in the general population. The objective of the present study was to determine cancer frequency in a cohort of patients with diabetes and to examine demographic, clinical, and quality of life differences between cancer survivors and their cancer-free peers to inform better individualized care. Methods:Self-reported survey data from 3,466 registrants with type 2 diabetes from Australia's National Diabetes Services Scheme (NDSS) were analyzed to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The validated European Organisation for Research and Treatment of Cancer–Quality of Life Questionnaire (EORTC-QLQ)-C30 was used to assess HRQoL [ 29 , 30 ]. As previous research shows that cancer patients with diabetes mainly score lower on physical function [ 7 , 10 , 11 ], general HRQoL [ 6 , 9 ], and vitality [ 9 ] as compared to those without diabetes, and to prevent type 1 errors as a result of multiple testing, only the global QoL, physical function, and fatigue scales were included in these analyses. All items were answered on a 4-point Likert scale ranging from ‘not at all’ to ‘very much’, while the questions regarding global QoL were scored on a 7-point scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validated European Organisation for Research and Treatment of Cancer–Quality of Life Questionnaire (EORTC-QLQ)-C30 was used to assess HRQoL [ 29 , 30 ]. As previous research shows that cancer patients with diabetes mainly score lower on physical function [ 7 , 10 , 11 ], general HRQoL [ 6 , 9 ], and vitality [ 9 ] as compared to those without diabetes, and to prevent type 1 errors as a result of multiple testing, only the global QoL, physical function, and fatigue scales were included in these analyses. All items were answered on a 4-point Likert scale ranging from ‘not at all’ to ‘very much’, while the questions regarding global QoL were scored on a 7-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies mainly reported a lower general HRQoL [ 6 , 9 ], physical function or mobility [ 7 , 10 ] and vitality [ 9 ] among cancer patients with diabetes, compared to cancer patients without diabetes. However, the majority of these studies focused on prostate cancer patients [ 8 , 9 , 11 , 12 ] and had a cross-sectional study design [ 6 , 7 , 9 11 ]. More importantly, only three studies adjusted their analyses for lifestyle factors [ 6 , 8 , 10 ], of which two only included body mass index (BMI) and no other lifestyle factors such as physical activity, smoking, or alcohol use [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…After applying the title keyword exclusion criteria, eliminating duplicates and excluding non-English language articles, 989 remained for preliminary review, of which 20 were retrieved for full review, and one additional article was identified from a search of the bibliographies. Upon full review, six were found not to include either the patient population or an outcome of interest, leaving 15 articles [ 13 20 , 24 30 ] for inclusion (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were six (40%; 95% CI, 34–46%) longitudinal cohort studies in which patients with pre-existing diabetes were followed from before to after incident diagnosis of cancer [ 15 , 16 , 24 27 ], six (40%; 95% CI, 34–46%) longitudinal cohort studies in which patients with diabetes were followed only after cancer [ 13 , 14 , 17 , 18 , 20 , 28 ] and three (20%; 95% CI, 15–25%) retrospective cross-sectional studies in which patients with historical diagnoses of diabetes and cancer were assessed for quality of care during a fixed window of time (usually one calendar year) after both diagnoses [ 19 , 29 , 30 ] ( Supplemental Materials, Table A ). The majority of studies (10/15: 67%; 95% CI, 61–73%) were from the USA [ 13 16 , 18 20 , 24 , 25 , 27 ], with two from the Netherlands [ 26 , 28 ], and one each from Australia [ 30 ], Korea [ 29 ] and the UK [ 17 ]. The most common types of cancers studied were breast (8/15: 53%; 95% CI, 47–60%) [ 13 , 15 , 17 , 18 , 24 , 25 , 27 , 30 ], colorectal (5/15: 33%; 95% CI, 27–39%) [ 13 , 15 17 , 20 ] and prostate (4/15: 27%; 95% CI, 21–32%) [ 13 , 15 , 17 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a retrospective study showed higher pathological response rates after neo-adjuvant chemotherapy in diabetic breast cancer patients treated with metformin compared to diabetic patients not treated with metformin Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/12/15 5:14 PM [166]. Others, however, fail to show this favorable association [167,168]. The potential of metformin as an anticancer drug lies in its capacity to activate AMP-activated protein kinase leading to downregulation of mTOR and subsequent inhibition of protein synthesis, cell proliferation, and growth [169].…”
Section: Therapeutic Possibilities For Targeting Adipose Tissue In Brmentioning
confidence: 86%